Manufacturing method of sheet for solid secondary battery and binder for solid secondary battery
Patent Information
- Application Number
- JP2022103333
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2022-06-28
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for manufacturing secondary battery sheets using lithium containing fibrillated polytetrafluoroethylene (PTFE) as a binder result in high resistance and uneven distribution of components, leading to decreased strength and flexibility of the electrode.
A method for producing a solid secondary battery sheet using a binder composed of polytetrafluoroethylene resin and a conductive aid, such as ketjen black or carbon nanotubes, which is uniformly mixed without a liquid medium, and is characterized by a specific F/C ratio and fibril diameter, ensuring even distribution and reduced resistance.
The method reduces the electrical resistance of the secondary battery sheet, enhances its strength and flexibility, and maintains proper conductivity, particularly suitable for lithium ion secondary batteries.
Smart Images

Figure 00000025_0000
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a method for manufacturing a sheet for solid-state secondary batteries and a binder for solid-state secondary batteries. [Background technology]
[0002] Fibrillated polytetrafluoroethylene (PTFE) is subjected to a lithium-ion electrolyte containing a non-aqueous electrolyte. It is being considered for use as a binder in the electrodes of a microion battery. (Patent Document 1) ).
[0003] Furthermore, it is also possible to obtain a uniform mixed powder by spray drying, in which conductive material is mixed with PTFE. This is shown (Patent Documents 2-4). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Special Publication No. 2017-517862 [Patent Document 2] Japanese Patent Application Publication No. 6-316784 [Patent Document 3] Japanese Patent Publication No. 2008-140809 [Patent Document 4] International release 2020 / 170797 [Patent Document 5] Japanese Patent Publication No. 2020-115485 [Overview of the project] [Problems that the invention aims to solve]
[0005] This disclosure relates to a sheet for secondary batteries using PTFE, and aims to reduce the resistance of the sheet. A method for manufacturing a sheet for a solid secondary battery that can achieve the strength of the composite sheet and The objective is to provide a binder for solid-state secondary batteries. [Means for solving the problem]
[0006] This disclosure relates to a uniform mixture of polytetrafluoroethylene resin and a conductive additive, and contains an active material. For creating secondary battery sheets that substantially do not contain a liquid medium, using a binder that is a powder. A method for manufacturing a sheet for a solid-state secondary battery, characterized by comprising a step (1) of preparing a composition. That is the case. This disclosure relates to polytetrafluoroethylene resin and Ketjenblack and / or caramel Electrodes that are substantially free of liquid medium using a binder containing a mixed powder of von nanotubes. A non-aqueous electrolyte is used, characterized by having a step (1) of preparing a composition for production. This is also a method for manufacturing electrodes for the next generation of batteries.
[0007] The above-mentioned binder preferably has a moisture content of 1000 ppm or less. The above binder is made by mixing a polytetrafluoroethylene resin and a conductive additive in the presence of a liquid medium. It is preferable that the product is manufactured by a manufacturing method that includes step (A) of causing the product to be produced. The above liquid medium is preferably water.
[0008] The upper binder is dried by spray drying the composition obtained in step (A) in step (B). It is preferable that the product is obtained by a manufacturing method having ) The above-mentioned PTFE preferably has a standard specific gravity of 2.11 to 2.20. The composition for creating secondary battery sheets preferably contains a positive electrode active material. The above-mentioned secondary battery is preferably a lithium-ion secondary battery.
[0009] The above electrode preferably has a fibrous structure with a fibril diameter (median) of 20 nm or more. stomach. The above binder has an elemental ratio of fluorine to carbon (F / C ratio) of 0, as measured by elemental analysis. It is preferable that the value is between 0.4 and 3.0.
[0010] This disclosure relates to a composition comprising a polytetrafluoroethylene resin and a conductive additive, It is also a binder for solid-state secondary batteries, characterized by being a powder that does not contain electrode active material. The above binder has an elemental ratio of fluorine to carbon (F / C ratio) of 0, as measured by elemental analysis. It is preferable that the value is between 0.4 and 3.0. This disclosure relates to polytetrafluoroethylene resin and Ketjenblack and / or caramel A binder for solid secondary battery electrodes, characterized by containing a mixed powder with bon nanotubes. There are also others. This disclosure is also characterized by containing the above-mentioned binder for secondary battery electrodes. This disclosure also relates to an electrode mixture characterized by containing the above-mentioned binder for secondary battery electrodes. . This disclosure also relates to an electrode characterized by having the above-mentioned electrode mixture. [Effects of the Invention]
[0011] In this disclosure, the electrical resistance value of the sheet is described for a secondary battery sheet using PTFE. A sheet for solid-state secondary batteries that can lower the strength while also being highly durable. We can provide a manufacturing method and a binder for solid-state secondary batteries. [Brief explanation of the drawing]
[0012] [Figure 1] This is a schematic diagram showing a cross-section of a cell used for measuring ionic conductivity. [Modes for carrying out the invention]
[0013] The details of this disclosure are described below. Mixtures using PTFE as a binder sometimes resulted in higher sheet resistance. The demonstration shows how to resolve such problems and obtain a sheet with a low resistance value. The present invention provides a method for manufacturing sheets for solid-state secondary batteries.
[0014] Combinations that use PTFE as a binder are formed by fibrillating the PTFE. It produces an adhesive effect. However, if electrodes are manufactured by mixing PTFE and a conductive additive as separate powders, The electrode may become highly resistive. This is because the PTFE is unevenly distributed within the electrode, affecting the conductivity. It is presumed that this is because the pathway is not sufficiently formed. Furthermore, a segregation of components occurs within the electrode. If this is the case, it can cause a decrease in electrode strength. On the other hand, if the mixture is kneaded vigorously to eliminate uneven distribution If this happens, excessive fibrillation of PTFE occurs, leading to a decrease in flexibility and strength. Therefore, use a binder that prevents uneven distribution of PTFE and conductive additives. This solves such problems. Furthermore, such binders can be used in solid-state secondary batteries. It can also be suitably used in the formation of the electrolyte layer. The electrolyte layer does not use an active material. A thin layer has been formed on it. When manufacturing such an electrolyte layer sheet, Electrical properties are considered a crucial issue. In particular, in the case of solid-state batteries, since there is no liquid medium, electrolysis is a problem. It is important that the layer sheet maintains appropriate conductivity, and for that purpose, the conductivity of the sheet Controlling this is important.
[0015] The present disclosure relates to a method for manufacturing a sheet for a solid-state secondary battery, and involves a polytetrafluoroethylene resin and a conductive It is characterized by the use of a binder, which is a powder that does not contain an active material and requires an auxiliary agent. Hereafter, this will be referred to as the first binder of this disclosure.
[0016] On the other hand, regarding the active material, if you try to mix PTFE and the conductive additive beforehand, it becomes a liquid. In the battery medium, moisture causes lithium to leach from the active material, leading to degradation of the active material and a decrease in battery capacity. It is known that this can lead to problems such as increased battery resistance (Patent Document 5). The binder used does not contain an active material and consists of a composition that requires PTFE and a conductive additive. By doing so, the objectives of this disclosure can be achieved without being limited by the active material.
[0017] Furthermore, polytetrafluoroethylene resin and Ketjenblack or carbon nanotubes Using a mixed powder with the obe as a binder is preferable because it can reduce electrode resistance. Such a binder can also achieve the objectives of this disclosure. The effect is not obtained when using other carbon-based conductive additives such as acetylene black. This is an effect that cannot be achieved. Such a binder will be referred to as the second binder of this disclosure.
[0018] The method for manufacturing a sheet for a solid-state secondary battery according to this disclosure is a composition that requires PTFE and a conductive additive. It is characterized by using a binder that is a powder that does not contain an active material. Furthermore, the particles constituting the powder do not consist solely of PTFE and conductive additives, but rather of PTFE and conductive additives. The present disclosure comprises a composition containing both an electrolytic agent. The manufacturing method involves using polytetrafluoroethylene resin and Ketjenblack or carbon nano The mixed powder with the tube may also be used as a binder. The following provides a detailed description of such binders and the components they contain.
[0019] (Polytetrafluoroethylene resin) In this disclosure, the PTFE is not particularly limited and may be a homopolymer. It may be a copolymer that can be fibrillated, but homopolymers are more preferred. It's nice. In the case of copolymers, the fluorine atom-containing monomer that is the comonomer is chlorotrifluor. Fluoroethylene, hexafluoropropylene, fluoroalkylethylene, perfluoroethylene Examples include chloroethylene, fluoroalkyl fluorovinyl ethers, and the like.
[0020] The PTFE used as a raw material when preparing the mixture described herein has a standard specific gravity of 2.11 to 2.20. It is preferable that the standard specific gravity is within that range, thereby providing a highly effective mixture. It has the advantage of being able to produce a treadmill. The lower limit of the standard specific gravity mentioned above is 2.12 or higher. It is more preferable that the upper limit of the standard specific gravity is 2.19 or less. It is even more preferable that the value be 2.18 or less.
[0021] Standard specific gravity [SSG] was obtained by preparing the sample in accordance with ASTM D-4895-89. The specific gravity of the sample is measured by the water displacement method.
[0022] The PTFE used in this disclosure may have a core-shell structure. Examples of PTFE include a core of high molecular weight polytetrafluoroethylene in the particles. And, lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene Examples include polytetrafluoroethylene containing a shell. Examples of oroethylene include the polyethylene described in Japanese Patent Publication No. 2005-527652. Examples include trafluoroethylene.
[0023] PTFE in powder form that satisfies the parameters described above can be obtained by conventional manufacturing methods. This is possible. For example, International Publication No. 2015-080291 and International Publication No. 2012-0 The manufacturing process should follow the instructions in publication number 86710, etc.
[0024] (Conductive additive) Any known conductive material can be used as the conductive additive mentioned above. A specific example is copper. , metal materials such as nickel, graphite such as natural graphite and artificial graphite, acetylene Rack, Ketchen Black, Channel Black, Furnace Black, Lamp Black Carbon black such as thermal black, needle coke, carbon nanotubes Carbon nanohorns, carbon nanofibers, fullerenes and graphene, VG Examples include carbon materials such as amorphous carbon (CF). Acetylene black is particularly preferred. These can be used individually, or two or more can be combined in any combination and ratio. It may be used. Examples of commercially available carbon black include Toka Black #4300. #4400, #4500, #5500 etc. (manufactured by Tokai Carbon Co., Ltd., Furnace Black), Lintex L etc. (manufactured by Degussa, Furnace Black), Raven 7000, 5750 , 5250, 5000ULTRAIII, 5000ULTRA etc., Conductex SC ULTRA, Conductex 975ULTRA, etc., PUER BLACK1 00, 115, 205 etc. (Columbian brand, Furnace Black), #2350, #2 400B, #2600B, #30050B, #3030B, #3230B, #3350B #3400B, #5400B, etc. (manufactured by Mitsubishi Chemical Corporation, Furnace Black), MONARC H1400, 1300, 900, VulcanXC-72R, BlackPearls2 000, LITX-50, LITX-200, etc. (Manufactured by Cabot, Furnace Black) , Ensaco250G, Ensaco260G, Ensaco350G, Super- P Li (IMERYS, Furnace Black), Ketjen Black ECP, EC P-600JD, Lionite CB, etc. (manufactured by Lion Specialty Chemicals, etc.) (Denka Black), Denka Black HS-100, Li-100, FX-35 (Denka Examples include acetylene black manufactured by [company name]. Commercially available VGCF includes VGCF- Examples include H (manufactured by Showa Denko Corporation). Commercially available multi-walled carbon nanotubes include FT7. Examples include 000 (manufactured by CNano). As a multi-walled carbon nanotube, the average outer diameter The fiber size is preferably 12 nm to 7 nm. The average fiber length is preferably 1 to 20 μm. This allows for good conductivity to be obtained. Even when a conductive additive is added and mixed in during the manufacturing of the composite sheet, That's fine.
[0025] The binder of this disclosure contains the above-mentioned conductive additive in a proportion of 1.0 to 60.0 by mass relative to the total amount of the binder. It is preferable to have this feature. This allows for good conductivity and sheet strength to be obtained. The lower limit above is more preferably 1.5 or higher, and even more preferably 2.0 or higher. It is preferable that the above upper limit be 55.0 or higher, and 50.0 or lower. That is even more preferable.
[0026] Furthermore, in this disclosure, it is essential that the binder contains a conductive additive, When manufacturing a composite sheet using a composite agent, PTFE and conductive additives are further added and mixed in. It is acceptable to use it.
[0027] The above conductive additive is usually present in the mixture at a concentration of 0.1% by mass or more, preferably 0.5% by mass or more. Preferably 0.8% by mass or more, and usually 50% by mass or less, preferably 30% by mass. More preferably, it is used in a content of 15% by mass or less. If the content is lower than this range, conductivity may be insufficient. Conversely, if the content is higher than this range... This may cause a decrease in battery capacity.
[0028] When mixing conductive additives with PTFE, materials added as needed include conductive materials and ions. Examples include powders and thickeners. For example, as a thickener, carboxymethylcellulose ( Celluloses such as CMC and methylcellulose (MC) can be suitably used.
[0029] When using these conductive additives and components other than PTFE, the amount of such components to be included is... Preferably, the proportion is 5.0% by mass or less relative to the total amount of binder. If the amount of this component exceeds 5.0% by mass, the objectives of the present invention may not be fully achieved.
[0030] (Binding agent) The binder used in this disclosure is a composition comprising PTFE and a conductive additive as essential components in powder form. This is the resulting shape. In other words, the composition is a mixture of PTFE and a conductive additive. It is in powder form, and the mixture of PTFE powder and conductive additive powder is included. No. This condition is not particularly limited, but granulation by spray drying It is particularly preferable that the particles are in a conditioned state.
[0031] The above binder contains PTFE and a conductive additive in a weight ratio of 99:1 to 50:50. It is preferable that the above mixing ratio is preferably 95:5 to 60:40. Preferably, the ratio is 90:10 to 70:30.
[0032] The method for manufacturing the above-mentioned binder is not particularly limited and can be manufactured by any method, however The manufacturing method also includes a step (A) of mixing PTFE and a conductive additive in the presence of a liquid medium. It is preferable that it is manufactured by [a specific method]. In this case, powder in a liquid dispersion of PTFE A method of adding and mixing a conductive additive, a liquid dispersion of PTFE and a liquid dispersion of the conductive additive. Methods such as mixing the body with other substances can be cited. Mixing can be done using general methods. For example, a disperser, homomixer, Examples include planetary mixers and other mixers, homogenizers, and wet jet mills. However, this is not limited to these.
[0033] In the above process (A), a dispersion containing PTFE, a conductive additive, and a liquid medium is used. The dispersion is such that the total amount of PTFE and conductive additive is PTFE, conductive additive and The amount is preferably 1 to 60% by weight of the total amount of liquid medium. The lower limit is 2 by weight. It is more preferable that it be %, and even more preferable that it be 3% by weight. The above upper limit is 50% by weight. It is more preferable that the amount be %, and even more preferable that it be 30% by weight.
[0034] By mixing these in a liquid medium, PTFE and conductive additives can be mixed with high uniformity. This is preferable in terms of its properties. The liquid medium in such a mixture is preferably water.
[0035] In this case, the PTFE used as a raw material is an aqueous dispersion obtained by emulsion polymerization. It is preferable to do so.
[0036] The PTFE used as a raw material for the above-mentioned binder is a compound that offers higher strength and superior homogeneity. Since a sheet of the agent can be obtained, it is preferable that the average primary particle diameter is 150 nm or larger. More preferably, it is 180 nm or more, even more preferably 210 nm or more, and particularly preferred The wavelength is 220 nm or greater. The larger the average primary particle size of PTFE, the higher the extrusion pressure when using that powder for extrusion molding. The increase in force can be suppressed, and it also has excellent moldability. There is no particular upper limit, but 500 nm is Good. From the viewpoint of productivity in the polymerization process, the upper limit is preferably 350 nm.
[0037] The above average primary particle size was determined using an aqueous dispersion of PTFE obtained by polymerization, and the polymer concentration Transmittance of 550 nm projected light per unit length of an aqueous dispersion adjusted to 0.22 mass% This is compared with the average primary particle diameter determined by measuring the directional diameter in transmission electron microscope images. A quantity curve is created, the transmittance of the aqueous dispersion to be measured is measured, and the calibration curve is created. It can be determined based on this.
[0038] The mixture of PTFE and conductive additive mixed in the liquid medium by the above step (A) is then, It is preferable that the liquid medium is removed by drying by spray drying (step (B)). It seems so. Drying methods include, for example, shelf dryers, vacuum dryers, freeze dryers, hot air dryers, and drums. Examples include dryers and spray dryers. Spray drying is particularly preferred. Spray drying is a method of drying liquid This method involves spraying a mixture of materials and solids into a gas and rapidly drying it to produce a dry powder. . This makes it possible to obtain a binder in powder form in which PTFE and a conductive additive are uniformly mixed. Spray drying is a generally well-known method and can be performed using any known apparatus. This can be done using a general method. The above step (B) is a general method using a known general apparatus. This can be done by the following method. The drying temperature should be, for example, in the range of 100°C to 250°C. This is preferable. At temperatures above 100°C, the solvent can be sufficiently removed, and at temperatures below 250°C... This is preferable as it can further reduce energy consumption. A drying temperature of 110°C or higher is more preferable. A temperature of 220°C or lower is more preferable. The amount of supply liquid depends on the scale of production, but for example, The flow rate may be in the range of 0.1 L / h to 2 L / h. Also, the nozzle used to spray the prepared solution... The size depends on the scale of production, but for example, the diameter range is between 0.5 mm and 5 mm. That's good too.
[0039] The binder obtained in this way preferably has a moisture content of 1000 ppm or less. stomach. Because the moisture content is less than 1000 ppm, it exhibits low gas generation as an initial characteristic. It is preferable in that it can be used to manufacture rechargeable batteries. The above moisture content is more preferably 500 ppm or less.
[0040] [Measurement of moisture content] The moisture content of the binder is measured using a Karl Fischer moisture meter (AD) equipped with a boat-type moisture vaporizer. Using the P-511 / MKC-510N (manufactured by Kyoto Electronics Manufacturing Co., Ltd.), a moisture vaporizer was used for 21 The water vaporized by heating to 0°C was measured. Nitrogen gas was used as the carrier gas at a flow rate of 20°C. The mixture was flushed at 0 mL / min, and the measurement time was set to 30 min. Also, Karl Fischer reagent and ChemAqua was used. The sample volume was 1.5g.
[0041] The second binder of this disclosure is a polytetrafluoroethylene resin and Ketjenblack and It is a mixed powder with / or carbon nanotubes. Such a mixed powder contains a binder and When used in this way, acetylene braces can reduce electrode resistance and improve battery characteristics. This is preferable to using well-known carbon conductive additives such as buck, and the first method described above It can be used in the same way as a binder.
[0042] In the second binder described above, Ketjenblack and / or carbon nano The tube is not particularly limited and the above-mentioned ones can be used. Furthermore, carbon The nanotubes are preferably multilayered, and more specifically, have an average fiber length of 1 to It is preferable to use one that is 20 μm in size.
[0043] The polytetrafluoroethylene used in the second binder described above is the first binder described above. The same type of agent can be used.
[0044] The second binder described above is obtained through the same process (A) and (B) described above as the first binder described above. It may be something that can be produced, or it may be something obtained by simply mixing these components. stomach. In the electrode fabrication compositions described in detail below, both the first binder and the second binder are the same. It can be used in the following way.
[0045] (Composition for creating secondary battery sheets) The composition for creating secondary battery sheets contains all the essential components for secondary battery sheets. This means a composition containing the above-mentioned binder, and other components (at the electrode). "Composition" refers to a composition in which electrode active materials, etc., are mixed together. Composition for creating secondary battery sheets. If it is an electrode composition, in addition to the above binder, an electrode active material and additional electrodes may be added. This composition contains electrolytic agents and the like.
[0046] (electrode active material) The above positive electrode active material is one that is electrochemically capable of intercepting and releasing alkali metal ions. There are no particular restrictions as long as it contains an alkali metal and at least one transition metal. The substance is preferred. Specific examples include alkali metal-containing transition metal composite oxides and alkali metals. Examples include transition metal phosphate compounds and conductive polymers. In particular, as a positive electrode active material, alkali metal-containing transition metal composites that generate high voltage are especially desirable. Oxides are preferred. Examples of alkali metal ions include lithium ions and sodium ions. Examples include potassium ions. In a preferred embodiment, alkali metal ions are, It may be a thium ion. That is, in this embodiment, the alkali metal ion secondary battery is a thium ion. It is a lithium-ion secondary battery.
[0047] Examples of the alkali metal-containing transition metal composite oxides mentioned above include: Formula: M a Mn 2-b M 1 b O4 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K) ; 0.9 ≤ a; 0 ≤ b ≤ 1.5; M 1 is selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, C r, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, at least one metal), represented by an alkali metal - manganese spinel composite oxide, Formula: MNi M 1-c M 2 c O2 (where M is at least one metal selected from the group consisting of Li, Na and K ; 0 ≤ c ≤ 0.5; M 2 is selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti , Mg, Ca, Sr, B, Ga, In, Si and Ge, at least one metal selected), represented by an alkali metal - nickel composite oxide, or, Formula: MCo M 1-d M 3 d O2 (where M is at least one metal selected from the group consisting of Li, Na and K ; 0 ≤ d ≤ 0.5; M 3 is selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti , Mg, Ca, Sr, B, Ga, In, Si and Ge, at least one metal selected) represented by an alkali metal - cobalt composite oxide. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.
[0048] Among them, from the point that a secondary battery with high energy density and high output can be provided, MCoO2, MMnO2, MNiO2, MMn2O4, MNi 0.8 Co 0.15 Al 0.05 O2, or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 is preferred and is represented by the following general formula (3). It is preferable that the compound is such that... MNi h Co i Mn j M 5 k O2(3) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K) M 5 is Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga It represents at least one selected from the group consisting of In, Si and Ge, (h+i+j+ k) = 1.0, 0 ≤ h ≤ 1.0, 0 ≤ i ≤ 1.0, 0 ≤ j ≤ 1.5, 0 ≤ k ≤ 0.2. .)
[0049] Examples of the alkali metal-containing transition metal phosphate compounds mentioned above include the following formula (4): M e M 4 f (PO4) g (4) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K) M 4 A small amount is selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni, and Cu. At the very least, one compound is shown, and the compounds represented by (0.5 ≤ e ≤ 3, 1 ≤ f ≤ 2, 1 ≤ g ≤ 3) can be listed. In the above, M is preferably selected from the group consisting of Li, Na, and K. It is one type of metal, more preferably Li or Na, and even more preferably Li. ru.
[0050] Examples of transition metals in lithium-containing transition metal phosphate compounds include V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred, and specific examples include LiFePO4, Li3Fe Iron phosphates such as 2(PO4)3 and LiFeP2O7, and cobalt phosphates such as LiCoPO4 These lithium transition metal phosphate compounds consist of some of the transition metal atoms, such as Al and T. i, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Examples include those substituted with other elements such as silicon. The lithium-containing transition metal phosphate compound described above is preferably one having an olivine-type structure. stomach.
[0051] Other cathode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 F e 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3 (formula In this case, M is at least one metal selected from the group consisting of Li, Na, and K. These include, in particular, M2MnO3, MNi 0.5 Mn 1.5 The positive electrode active material, such as O2, When a secondary battery is operated with a voltage exceeding 4.4V or a voltage of 4.6V or higher, This is preferable in that the crystal structure does not collapse. Therefore, a positive electrode material containing the positive electrode active material exemplified above is used. Electrochemical devices such as secondary batteries maintain their remaining capacity even when stored at high temperatures. Furthermore, the rate of resistance increase is not easily affected, and the battery performance does not deteriorate even when operated at high voltage. ,preferable.
[0052] Other positive electrode active materials include M2MnO3 and MM 6 O2(wherein M is Li, Na and K) At least one metal selected from the group consisting of M6 include solid solution materials with transition metals such as Co, Ni, Mn, F e, etc.
[0053] As the above solid solution material, for example, an alkali metal manganese oxide represented by the general formula Mx[Mn(1-y)M'y]Oz is used. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M' consists of at least one 7 metal element other than M and Mn. For example, it contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and S n. Also, the values of x, y, and z in the formula are in the ranges of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, a manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-dissolved based on Li2MnO3 such as Li1 Mn .2 Co 0.5 Ni 0.14 O2 is preferable because it can provide an alkali metal ion secondary battery having a high energy density. 0.14 Also, it is preferable to include lithium phosphate in the positive electrode active material because the continuous charging characteristics are improved. Although there is no limitation on the use of lithium phosphate, it is preferably used by mixing the above positive electrode active material and lithium phosphate. The amount of lithium phosphate used is such that the lower limit is preferably 0.1% by mass or more, more preferably
[0054] 0.3% by mass or more, still more preferably 0.5% by mass or more, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, still more preferably 5% by mass or less, based on the total of the above positive electrode active material and lithium phosphate.
[0055] The conductive polymers mentioned above include p-doped conductive polymers and n-doped conductive polymers. Examples of conductive polymers include polyacetylene-based and polyphenylene-based polymers. Examples include heterocyclic polymers, ionic polymers, ladder and network polymers, and the like. .
[0056] Furthermore, a positive electrode active material may be used in which a substance with a different composition is attached to its surface. i. Surface-adhering substances include aluminum oxide, silicon oxide, titanium oxide, and zirconium oxide. Magnesium oxide, calcium oxide, boron oxide, antimony oxide, bismuth oxide, etc. Oxides, lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate Sodium sulfates such as aluminum sulfate, lithium carbonate, calcium carbonate, magnesium carbonate Examples include carbonates such as um, and carbon.
[0057] These surface-adhering substances can be, for example, dissolved or suspended in a solvent and impregnated into the positive electrode active material, After addition, the method involves drying, or dissolving or suspending the surface-adhering substance precursor in a solvent to activate the positive electrode A method of impregnating or adding a substance and then reacting it by heating, etc., and adding to a positive electrode active material precursor. It can be attached to the surface of the positive electrode active material by methods such as adding and simultaneously firing it. When attaching a material, the carbonaceous material is mechanically attached afterwards, for example, in the form of activated carbon. Methods can also be used.
[0058] The amount of surface-adhering material is expressed in mass relative to the positive electrode active material, with a lower limit of preferably 0. The upper limit is 1 ppm or more, more preferably 1 ppm or more, even more preferably 10 ppm or more. Preferably, it is used in an amount of 20% or less, more preferably 10% or less, and even more preferably 5% or less. The surface-adhering substance can suppress the oxidation reaction on the surface of the positive electrode active material, thus extending the battery life. It can improve life. If the amount applied is too small, the effect will not be fully realized. If there is too much lithium, it can hinder the movement of lithium ions, potentially increasing resistance.
[0059] The particle shape of the positive electrode active material is not limited to the conventionally used shapes such as clumps, polyhedrons, spheres, or ellipsoids. Examples include plate-like, needle-like, and columnar shapes. Furthermore, primary particles aggregate to form secondary particles. That's good too.
[0060] The tap density of the positive electrode active material is preferably 0.5 g / cm³. 3 More preferably 0.8g / cm 3 More preferably 1.0 g / cm³ 3 That concludes the explanation. Tap density of the positive electrode active material If the above lower limit is not met, the required amount of conductive material and binder will increase during the formation of the positive electrode active material layer. The filling rate of the positive electrode active material into the positive electrode active material layer may be limited, which can restrict the battery capacity. By using composite oxide powder with high top density, a high-density positive electrode active material layer can be formed. This is possible. Generally, a higher tap density is preferable, and there is no particular upper limit, but if it is too high... Because the density may not pack down easily during pressing, and the load characteristics may be prone to deterioration, the upper limit is Preferably 4.0 g / cm³ 3 More preferably, 3.7 g / cm³ 3 The following are even better 3.5g / cm³ 3 The following applies: In this disclosure, the tap density is defined as 5-10 g of positive electrode active material powder mixed with a 10 ml glass scalpel. The powder filling density (tapping) when the cylinder is filled and tapped 200 times with a stroke of approximately 20 mm. (Patent density) g / cm³ 3 We will seek it as follows.
[0061] Median diameter d50 of positive electrode active material particles (when primary particles aggregate to form secondary particles) The secondary particle size is preferably 0.3 μm or larger, more preferably 0.5 μm or larger, and even more preferably The particle size is preferably 0.8 μm or larger, most preferably 1.0 μm or larger, and also preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, most preferably The size must be 22 μm or less. If the size falls below the above lower limit, it may not be possible to obtain a product with high tap density. If the upper limit is exceeded, the diffusion of lithium within the particles takes longer, leading to a decrease in battery performance. Problems such as the above may occur. Here, the positive electrode active material having different median diameters d50 By mixing two or more types, the packing properties during cathode fabrication can be further improved.
[0062] In this disclosure, the median diameter d50 is defined as a known laser diffraction / scattering particle size distribution analyzer. It is measured by the HORIBA LA-920 particle size analyzer. As the dispersion medium used during the process, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used. After 5 minutes of ultrasonic dispersion, the measurement is performed with a set refractive index of 1.24.
[0063] When primary particles aggregate to form secondary particles, the average primary particle diameter of the positive electrode active material is Preferably, it is 0.05 μm or larger, more preferably 0.1 μm or larger, and even more preferably The particle size is 0.2 μm or larger, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less. More preferably, it is 3 μm or less, and most preferably 2 μm or less. If it exceeds the above upper limit, it becomes spherical. It is difficult to form secondary particles, which negatively affects powder filling properties and significantly reduces the specific surface area. To achieve this, there is a higher possibility that battery performance, such as output characteristics, will deteriorate. Conversely, If the value falls below the lower limit, problems such as poor reversibility of charging and discharging usually occur because the crystal is underdeveloped. There are times when cheating is possible.
[0064] In this disclosure, the average primary particle diameter is measured by observation using a scanning electron microscope (SEM). It is determined. Specifically, in a photograph at 10,000x magnification, primary particles relative to a horizontal line. Find the longest intercept value between the left and right boundaries for any 50 primary particles, and then calculate the average value. It can be obtained by taking this.
[0065] The BET specific surface area of the positive electrode active material is preferably 0.1 m². 2 / g or more, more preferably 0.2 m 2 / g or more, more preferably 0.3m 2 The value is 1 / g or more, and the upper limit is preferably 50m 2 / g or less, more comfortable 40 m 2 / g or less, more preferably 30m 2 B is less than / g If the ET specific surface area is smaller than this range, battery performance tends to decrease, and if it is larger, tap density decreases. It becomes harder to raise the price.
[0066] In this disclosure, the BET specific surface area is calculated using a surface area meter (for example, a fully automatic surface area meter manufactured by Okura Riken Co., Ltd.). Using a controlled apparatus, the sample was pre-dried at 150°C for 30 minutes under nitrogen flow, A nitrogen-helium mixture precisely adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3. It is defined by a value measured using a gas and the nitrogen adsorption BET single-point method based on the gas flow method.
[0067] The secondary battery disclosed herein is a large lithium-ion secondary battery for hybrid vehicles and distributed power sources. When used in this context, high power output is required, so the particles of the positive electrode active material are mainly secondary particles. It is preferable that it be a body. The particles of the above positive electrode active material have an average particle diameter of 40 μm or less for secondary particles, and an average primary particle diameter of 40 μm or less. It is preferable that the mixture contains 0.5 to 7.0 volume percent of fine particles with a diameter of 1 μm or less. By including fine particles with a primary particle diameter of 1 μm or less, the contact area with the electrolyte is increased. This allows for faster diffusion of lithium ions between the active material and the electrolyte, As a result, the output performance of the battery can be improved.
[0068] For the production of the positive electrode active material, methods common to the production of inorganic compounds are used. Various methods can be considered to create spherical or ellipsoidal active materials, for example, transition Metal raw materials are dissolved or pulverized and dispersed in a solvent such as water, and the pH is adjusted while stirring. A spherical precursor is prepared and recovered, and after drying as needed, it is converted into LiOH, Li2CO3 Methods include adding a Li source such as LiNO3 and firing it at a high temperature to obtain an active material.
[0069] For the manufacture of the positive electrode, the positive electrode active material may be used alone, or two or more materials with different compositions may be used. They may be used in any combination or ratio. Preferred combinations in this case include: LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Combination with ternary systems such as O2 In addition, LiCoO2 and LiMn2O4, or a portion of the Mn in these, can be replaced with other transition metals, etc. A combination of these, or LiFePO4 and LiCoO2 or one of these Co Examples include combinations in which a portion is substituted with other transition metals, etc.
[0070] The content of the above-mentioned positive electrode active material is preferably 50-99.5% by mass in the positive electrode mixture for high battery capacity. More preferably, 80-99% by mass is preferred. Furthermore, the content of the positive electrode active material is preferably 80% by mass or more, more preferably 82% by mass or more. More preferably, it is 84% by mass or more. The upper limit is preferably 99% by mass or less. Preferably, it is 98% by mass or less. If the content of the positive electrode active material in the positive electrode mixture is low, the electrical capacity This may result in insufficient strength. Conversely, if the content is too high, the strength of the positive electrode may be insufficient.
[0071] The negative electrode active material is not particularly limited and includes, for example, lithium metal, artificial graphite, graphite carbon fiber, Carbon produced by resin firing, carbon grown in the pyrolysis vapor phase, coke, mesocarbon microbeads (MCMB) ), furfuryl alcohol resin calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon Fibers, natural graphite, carbonaceous materials such as non-graphitizable carbon, silicon, and silicon alloys. Silicon-containing compounds such as Li4Ti5O 12 Select one or more from the above. Examples of the above mixtures include those containing at least a portion of carbonaceous material. Alternatively, silicon-containing compounds can be used particularly favorably.
[0072] The negative electrode active material used in this disclosure preferably contains silicon as a constituent element. By including this element in the constituent elements, it is possible to create a high-capacity battery.
[0073] Silicon-containing materials include silicon particles and silicon nanoparticles dispersed in silicon-based compounds. Particles having a structure, silicon oxide particles represented by the general formula SiOx (0.5 ≤ x ≤ 1.6), and A mixture of these is preferred. Using these results in higher initial charge-discharge efficiency and high A negative electrode mixture for lithium-ion secondary batteries with high capacity and excellent cycle characteristics can be obtained.
[0074] In this invention, silicon oxide refers to a general term for amorphous silicon oxides, and silicon oxide before disproportionation. The element i is represented by the general formula SiOx (0.5 ≤ x ≤ 1.6). x is 0.8 ≤ x < 1.6. Preferably, 0.8 ≤ x < 1.3 is preferred. This silicon dioxide is, for example, silicon dioxide By heating a mixture of silicon and metallic silicon, silicon monoxide gas is produced, which is then cooled and precipitated to obtain silicon monoxide. It is possible.
[0075] Particles having a structure in which silicon nanoparticles are dispersed in a silicon-based compound include, for example, silicon fine particles. Methods of calcining a mixture of the material with a silicon-based compound, or disproportionation represented by the general formula SiOx The silicon dioxide particles are placed in an inert, non-oxidizing atmosphere such as argon at a temperature of 400°C or higher, preferably It can be obtained by heat treatment at a temperature of 800-1,100°C and carrying out a disproportionation reaction. The material obtained by the latter method is preferable because the silicon microcrystals are uniformly dispersed. Such disproportionation reactions can result in silicon nanoparticles with a size of 1 to 100 nm. Furthermore, regarding silicon dioxide in particles having a structure in which silicon nanoparticles are dispersed in silicon dioxide... In particular, silicon dioxide is desirable. Furthermore, silicon can be measured using a transmission electron microscope. It can be confirmed that nanoparticles (crystals) are dispersed in amorphous silicon dioxide.
[0076] The physical properties of silicon-containing particles can be appropriately selected depending on the desired composite particle. For example, The average particle size is preferably 0.1 to 50 μm, and more preferably 0.2 μm or larger at the lower limit. A thickness of 0.5 μm or more is even more preferable. The upper limit is more preferably 30 μm or less, and 20 μm or less is preferable. Furthermore, it is preferable. In this disclosure, the average particle size refers to the particle size distribution measurement by laser diffraction. This is expressed as the weight-average particle size in [location].
[0077] The BET specific surface area of silicon-containing particles is 0.5 to 100 m². 2 / g is preferred, 1 to 20m 2 / g is more preferable. BET specific surface area is 0.5m² 2 If the amount is greater than / g, the electrode is coated There is no risk of reduced adhesion and decreased battery performance. Also, 100m 2 / g or less If so, the proportion of silicon dioxide on the particle surface increases, making it suitable as a negative electrode material for lithium-ion secondary batteries. There is no risk of battery capacity decreasing when used in this manner.
[0078] By coating the silicon-containing particles mentioned above with carbon, conductivity is imparted, resulting in improved battery performance. As a method for imparting conductivity, a method of mixing with conductive particles such as graphite, the above Methods for coating the surface of silicon-containing particles with a carbon film, and methods combining both, etc. Examples include coating with a carbon film, and a preferred coating method is chemical vapor deposition (C The VD method is more preferable.
[0079] The amount of the above-mentioned negative electrode active material is set to 40% in the electrode mixture in order to increase the volume of the resulting electrode mixture. Preferably, it is % by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more. Yes. The upper limit is preferably 99% by mass or less, and more preferably 98% by mass or less.
[0080] (Other ingredients) The above-mentioned composition for creating secondary battery sheets may further contain a thermoplastic resin. Examples of resins include polyvinylidene fluoride, polypropylene, polyethylene, polystyrene, and poly Examples include polyethylene terephthalate and polyethylene oxide. One type is used alone. However, two or more types may be used in any combination and ratio.
[0081] The ratio of thermoplastic resin to electrode active material is usually 0.01% by mass or more, preferably 0.0 It is 5% by mass or more, more preferably 0.10% by mass or more, and usually 3.0% by mass or less. Preferably, the amount is in the range of 2.5% by mass or less, more preferably 2.0% by mass or less. By adding a resin, the mechanical strength of the electrode can be improved. Also, within this range If it exceeds this, the proportion of electrode active material in the electrode mixture decreases, leading to problems such as a decrease in battery capacity. This can sometimes lead to a problem where the resistance between the active materials increases.
[0082] (solid electrolyte) Even if the solid electrolyte used in the solid secondary battery mixture of this disclosure is a sulfide-based solid electrolyte, Alternatively, an oxide-based solid electrolyte may be used. In particular, when using a sulfide-based solid electrolyte, flexibility is important. It has the advantage of being sexual.
[0083] The above sulfide-based solid electrolyte is not particularly limited, and includes Li2S-P2S5, Li2S-P 2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-Si S2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO 4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4S iO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3. 4P 0.6 Si 0.4 S4, Li3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x One of the following selected from S4, Li6PS5Cl, etc., or a mixture of two or more of them. You can use it.
[0084] The above sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte contained in this product is used in solid-state batteries that use lithium ions as carriers. It is used as an electrochemical device with high energy density, and is particularly preferred in that respect. It is a rare thing.
[0085] The above oxide-based solid electrolyte contains an oxygen atom (O) and belongs to Group 1 or Group 2 of the periodic table. A compound that possesses the ionic conductivity of a metal belonging to the same category and also has electronic insulating properties is preferred.
[0086] Specific examples of compounds include, for example, Li xa La ya TiO3 [xa = 0.3~0.7] , ya = 0.3~0.7] (LLT), Li xb La yb Zr zb Mbb mb O nb (M bb is at least one of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, Sn One or more elements, xb satisfies 5 ≤ xb ≤ 10, yb satisfies 1 ≤ yb ≤ 4, z b satisfies 1 ≤ zb ≤ 4, mb satisfies 0 ≤ mb ≤ 2, and nb satisfies 5 ≤ nb ≤ 20. ) Li xc B yc Mcc zc O nc (Mcc is C, S, Al, Si, Ga, Ge, At least one element of In and Sn, where xc satisfies 0 ≦ xc ≦ 5, yc satisfies 0 ≦ yc ≦ 1, zc satisfies 0 ≦ zc ≦ 1, and nc satisfies 0 ≦ nc ≦ 6.). L i xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (However, 1 ≦ xd ≦ 3, 0 ≦ yd ≦ 2, 0 ≦ zd ≦ 2, 0 ≦ ad ≦ 2, 1 ≦ md ≦ 7, 3 ≦ nd ≦ 15), Li (3-2xe) Mee xe DeeO (xe represents a number from 0 to 0.1, and Mee represents a divalent metal atom. Dee represents a halogen atom or a combination of two or more halogen atoms ).), Li xf Si yf O zf (1 ≦ xf ≦ 5, 0 < yf ≦ 3, 1 ≦ zf ≦ 10 ), Li xg S yg O zg (1 ≦ xg ≦ 3, 0 < yg ≦ 2, 1 ≦ zg ≦ 10), Li3B O3 - Li2SO4, Li2O - B2O3 - P2O5, Li2O - SiO2, Li6Ba La2Ta2O 12 、Li3PO (4-3 / 2w) N w (w is w < 1), LISICON (Lithium super ionic conductor) having a crystal structure of [[ID=%56]]Li 3.5 Zn 0.25 GeO4, having a perovskite crystal structure of La 0.51 Li 0.34 TiO 2.94 、La 0.55 Li 0.35 TiO3, NASICON (Nat rium super ionic conductor) having a crystal structure of LiTi 2P3O 12Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh Si yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), it has a garnet-type crystal structure. Li7La3Zr2O 12 Examples include (LLZ). Furthermore, the elemental configuration relative to LLZ Ceramic materials that have undergone substitution are also known. For example, Mg(magnesium) is used in relation to LLZ. Um) and A (A is Ca (calcium), Sr (strontium), Ba (barium) Substitution of at least one element with at least one element selected from the group comprising The LLZ-type ceramic materials used are also mentioned. Furthermore, phosphorus compounds containing Li, P, and O are also mentioned. This is also desirable. For example, lithium phosphate (Li3PO4), some of the oxygen in lithium phosphate is nitrogen LiPON and LiPOD1 (where D1 is Ti, V, Cr, Mn, Fe, Co) are substituted with elemental compounds. A small number of materials selected from Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. Examples include (and one other type). Also, LiA 1 ON(A 1 These are Si, B, Ge, Al, C At least one selected from Ga, etc., can also be preferably used. For example, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, Examples include Li2O-Al2O3-SiO2-P2O5-TiO2.
[0087] The above oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte it contains is used in solid-state batteries that use lithium ions as carriers. It is used as an electrochemical device with high energy density, and is particularly preferred in that respect. It is a rare thing.
[0088] The above oxide-based solid electrolyte is preferably an oxide having a crystalline structure. The oxides possessing these properties are particularly preferable in terms of their good Li ion conductivity. As for oxides having a crystalline structure, there are perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3 etc. ), Garnet type (Li7La3Zr2O 12 Examples include (LLZ, etc.). However, the NASICON type is preferable.
[0089] The volume-average particle size of oxide-based solid electrolytes is not particularly limited, but it is 0.01 μm or larger. It is preferable that the particle size be 0.03 μm or larger, and more preferably 0.03 μm or larger. The upper limit is 100 μm. The following is preferable, and more preferably 50 μm or less. The average particle size of solid electrolyte particles is measured using the following procedure: Oxide-based solid electrolyte particles are subjected to water... Disperse the substance at 1% by mass in a 20 ml sample bottle using heptane (if the substance is unstable in water). Dilute the solution. Irradiate the diluted dispersed sample with 1 kHz ultrasound for 10 minutes, and immediately afterwards... This dispersion sample will be used for testing. Using a -920 (manufactured by HORIBA), data was collected at a temperature of 25°C using a quartz cell. The sample is taken 50 times to obtain the volume-average particle size. Other detailed conditions will be specified in the JIS as needed. Refer to the description in SZ8828:2013 "Particle Size Analysis - Dynamic Light Scattering Method". Per level Prepare five samples and use their average value.
[0090] The binder for a solid secondary battery of the present disclosure is particularly suitable for a lithium-ion solid secondary battery. It is also suitable for a sulfide solid secondary battery. When the binder for a solid secondary battery of the present disclosure is used in a solid secondary battery, it is usually in the form of a sheet. It is used in this form.
[0091] The binder sheet for a solid secondary battery of the present disclosure can be used as a positive electrode sheet or a negative electrode sheet. Furthermore, it can be used as a sheet for a solid electrolyte layer. Among these, when used as an electrode sheet, it further contains active material particles. The active material particles can be a positive electrode active material or a negative electrode active material. The sheet for a solid secondary battery of the present disclosure can be more preferably used as a positive electrode sheet using a positive electrode active material. Also, when used as an electrode sheet, it may contain a conductive aid as necessary.
[0092] (Method for manufacturing an electrode) <00009 By utilizing this fibrillating property, PTFE can be used as a binder. Yes, it is possible. In other words, the fibrillated PTFE becomes entangled with other powder components, The PTFE binds the powder components together, thereby acting as a binder when molding the powder components. It can act in this way.
[0093] Furthermore, even when using fibrillated PTFE as a binder, sufficient fibrillation is necessary. Otherwise, it will not be able to perform well when used as an electrode mixture. or fine fibrillation processing such as having a fibrous structure with a fibril diameter of 20 nm or more By performing this process, fibrillated PTFE exhibits good properties as a binder for electrode mixtures. It is capable of demonstrating its capabilities.
[0094] The above composition for creating secondary battery sheets preferably contains substantially no liquid medium. In the electrode obtained by the disclosed manufacturing method, the fibrous structure has a fibril diameter of 20 nm or more. It is preferable that the material has PTFE having a structure as a component. The fibril diameter (median) (hereinafter simply referred to as "fibril diameter") is 20 nm or larger. This is preferable. That is, PTFE with a small fibril diameter is present in the electrode in this way. This is preferable because it has the effect of binding the powder components that make up the electrode together and provides flexibility. That is the case.
[0095] The fibril diameters mentioned above were measured using the following method. (1) Magnification of the compound sheet using a scanning electron microscope (S-4800 model, manufactured by Hitachi, Ltd.) Take a photograph (7000x magnification) and obtain the image. (2) Draw two lines at equal intervals horizontally on this image to divide the image into three equal parts. (3) For all PTFE fibers on the upper straight line, measure the diameters at three positions for each PTFE fiber and take the averaged value as the diameter of the PTFE fiber. The three positions to be measured are the intersections of the PTFE fiber and the straight line, and the positions shifted 0.5 μm upward and downward respectively from the intersections. (Excluding unfibrillated PTFE primary particles). (4) Perform the operation in (3) for all PTFE fibers on the lower straight line. (5) Starting from the first image, move 1 mm to the right on the screen, take a picture again, and measure the diameter of the PTFE fiber by (3) and (4) above. Repeat this process and end when the number of measured fibers exceeds 80 pieces. (6) Take the median value of the diameters of all the measured PTFE fibers as the fibril diameter size.
[0096] The above fibril diameter is preferably 15 nm or more, more preferably 20 nm or more, and even more preferably 31 nm or more. If the fibrillation progresses too much, the flexibility tends to be lost. Also, the upper limit is not particularly limited, but from the perspective of flexibility, for example, it is preferably 150 nm or less, more preferably 100 nm or less, and particularly preferably 75 nm or less.
[0097] The method for obtaining PTFE having the above fibril diameter is not particularly limited, but for example, a step (2) of applying shear force while mixing the above composition for preparing the secondary battery sheet a step (3) of molding the mixture obtained in step (2) into a bulk shape, and a step (4) of rolling the bulk electrode mixture obtained in step (3) into a sheet shape can be mentioned.
[0098] Step (2) above involves mixing the composition for creating a secondary battery sheet obtained in step (1) above. This is a process of applying shear force while doing so. The powder components are mixed, and at the same time as mixing, shear force is applied to fibrillate the PTFE. It can also be used as a combination agent.
[0099] In such a method, for example, in step (2), the composition for creating a secondary battery sheet is By keeping the mixing conditions below 2000 rpm, flexibility can be maintained while controlling the PTFE's properties. By promoting librylation and controlling the applied shear stress, PT The fibril diameter of FE can be made to 20 nm or more.
[0100] Furthermore, after step (4), a larger load is applied to the resulting rolled sheet to make it even thinner. It is also preferable to have a step (5) in which the material is rolled into a sheet. That is also desirable. Furthermore, after step (4) or step (5), the obtained rolled sheet is roughly crushed and then subjected to further crushing. The fibril diameter can also be adjusted by having a step (6) of forming it into a U-shape and rolling it into a sheet. It is possible to adjust the process. It is preferable to repeat step (6) for at least 1 to 12 times.
[0101] In other words, by applying shear force, the PTFE powder is fibrillated, and this becomes active material The mixture can be manufactured by intertwining it with powder components such as quality. The method will be explained later.
[0102] In the electrode manufacturing method of this disclosure, the PTFE content is the ratio of PTFE in the electrode mixture and And usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 1.0% by mass It is % or more, and usually 50% by mass or less, preferably 40% by mass or less, and more preferably The amount is 30% by mass or less, most preferably 10% by mass or less. If the proportion of the binder is too low, The inability to adequately hold the material results in insufficient mechanical strength of the electrodes, degrading battery performance such as cycle characteristics. This can sometimes lead to problems. On the other hand, if the temperature is too high, it can lead to a decrease in battery capacity and conductivity. Yes. Furthermore, in the manufacturing method described in detail below, even when the first binder is used, the second binder... It can be used in the same way when an adhesive is used.
[0103] The electrode mixture of this disclosure can be used as a mixture for secondary batteries. In particular, the mixture of this disclosure The agent is suitable for lithium-ion secondary batteries. The mixture disclosed herein is typically used in sheet form when used in secondary batteries. .
[0104] The following is an example of a specific manufacturing method for a combination sheet containing a combination agent. In the electrode manufacturing method disclosed herein, the composite sheet is (0) A step of preparing a mixture containing an electrode active material and, if necessary, a conductive additive. The mixture obtained by step (0) above is used to prepare a composition for making a secondary battery sheet containing a binder. Manufacturing process (1) (2) A step in which shear force is applied while mixing the composition for creating the secondary battery sheet. Step (3) involves forming the mixture obtained in step (2) into a bulk form, and Step (4) is to roll the bulk mixture obtained in step (3) into a sheet. It can be obtained by a method for manufacturing a composite sheet for secondary batteries having [the specified characteristic].
[0105] In step (2) above, when shear force is applied while mixing the electrode fabrication composition, The resulting electrode fabrication composition is simply a mixture of electrode active material, binder, etc. It exists in an intangible state. Specific mixing methods include W-type mixers, V-type mixers, and D Ram-type mixer, ribbon mixer, conical screw-type mixer, single-shaft kneader, twin-shaft kneader, mixer Methods of mixing include using a Kussmaller, agitator, or planetary mixer. ru.
[0106] In step (2) above, the mixing conditions can be set appropriately by adjusting the rotation speed and mixing time. For example, The rotational speed is preferably 2200 rpm or less. Preferably 10 rpm or more. More preferably 15 rpm or higher, and even more preferably 20 rpm or higher. Also preferably The engine speed is 2000 rpm or less, more preferably 1800 rpm or less, and even more preferably 1500 rpm. This is within the pm range. Below this range, mixing will take longer and will affect productivity. This gives... Also, if it exceeds this, fibrillation proceeds excessively, resulting in electrodes with poor strength and flexibility. There is a risk of it becoming a combined drug sheet.
[0107] In step (3) above, "forming into a bulk form" means forming the electrode manufacturing composition into a single mass. It is. Specific methods for forming materials into bulk include extrusion molding and press molding. Furthermore, "bulk" does not refer to a specific shape, but rather to a single, solid mass. Any state is acceptable, and includes forms such as rod-shaped, sheet-shaped, spherical, and cube-shaped. The size is preferably such that the diameter of its cross-section or the smallest side is 10,000 μm or larger. i. More preferably, it is 20,000 μm or larger.
[0108] The specific rolling method in the above process (4) is a roll press, a flat plate press, and One method is rolling using a render roll machine or similar equipment.
[0109] Furthermore, after step (4), a larger load is applied to the resulting rolled sheet to make it even thinner. It is also preferable to have a step (5) of rolling it into a sheet. This is preferable. In this way, instead of thinning the rolled sheet all at once, it is done in stages, little by little. Rolling improves flexibility. The number of times step (5) is performed is preferably 2 to 10 times, and more preferably 3 to 9 times. It seems so. As for specific rolling methods, for example, two or more rolls are rotated and pressure is applied between them. Methods include processing the rolled sheet into a thinner sheet by passing it through the rolling process. It is desirable to heat it. The lower limit of the temperature range is preferably 40 degrees Celsius or higher, and preferably 50 degrees Celsius or higher. Preferably, it is 60 degrees or higher. The upper limit is preferably 300 degrees or lower, and 250 degrees. A temperature below 200 degrees Celsius is more preferable, and a temperature below 200 degrees Celsius is even more preferable. Heating softens the sheet. It can be easily rolled.
[0110] Furthermore, in terms of adjusting the fibril diameter, after process (4) or process (5), the rolling sheet The process may also include a step (6) in which the material is roughly crushed, then reshaped into a bulk form, and rolled into a sheet. It is preferable. It is also preferable to repeat step (6). The number of times step (6) is performed is one or more. Preferably 12 times or less, and more preferably 2 to 11 times or less.
[0111] In step (6), a specific method for crushing the rolled sheet and forming it into a bulk form is to crush the sheet. Methods of folding a rolled sheet, or forming it into a rod or thin film sheet, chip Methods such as pulverization are mentioned. In this disclosure, "crushing" means making the material into a sheet in the next step. To roll it, the shape of the rolled sheet obtained in step (4) or step (5) is changed to another shape. It means to change something, and includes cases such as simply folding a rolled sheet. ru.
[0112] Alternatively, step (5) may be performed after step (6), and this process may be repeated. Furthermore, in steps (3) to (4), (5), and (6), uniaxial stretching or biaxial stretching is performed. You can go. Furthermore, the fibril diameter can be adjusted by the degree of coarse crushing in step (6).
[0113] In the above steps (4), (5), or (6), the rolling ratio is preferably 10% or more, more preferably The percentage is 20% or more, preferably 80% or less, more preferably 65% or less. More preferably, it is in the range of 50% or less. Below the above range, as the number of rolling cycles increases This will take more time and affect productivity. Also, if it exceeds this, fibrillation will be excessive. This can progress to a point where the resulting composite sheet has poor strength and flexibility. The rolling ratio, as used here, refers to the percentage reduction in thickness after rolling compared to the thickness of the sample before rolling. It refers to the sample before rolling, even if it is a bulk composition for making secondary battery sheets, or a sheet. It may also be a composition. The thickness of the sample refers to the thickness in the direction in which the load is applied during rolling.
[0114] As mentioned above, PTFE powder fibrillates when shear force is applied. To obtain a fibrous structure with a fibril diameter of 20 nm or more, excessive shear stress is required. This can lead to excessive fibrillation, compromising flexibility. Also, it can result in weaker materials. The tensile stress may not be sufficient in terms of strength. Therefore, during mixing and rolling, it is necessary to apply an appropriate amount. Shear stress is applied to PTFE to promote fibrillation, and the resin is rolled and stretched into a sheet. By performing the above process within the specified range, fibrous material with a fibril diameter of 20 nm or more is produced. It may have a structure.
[0115] The composite sheet of this disclosure can be used as a composite sheet for secondary batteries. Negative electrode, positive electrode It can be either pole. In particular, the compound sheet of this disclosure is a lithium-ion secondary battery It is suitable for.
[0116] (positive electrode) In this disclosure, the positive electrode is composed of a current collector and an electrode mixture sheet containing the positive electrode active material. It is preferable that it be done. The materials used for the positive electrode current collector include aluminum, titanium, tantalum, stainless steel, and nickel. Metals such as carbon fiber, or alloys thereof; carbon fiber such as carbon cloth and carbon paper. Materials can be listed. Among them, metallic materials, particularly aluminum or its alloys, are preferred.
[0117] In terms of current collector shape, metal materials include metal foil, metal cylinder, metal coil, metal plate, and Examples include spand metal, punched metal, and foamed metal. In the case of carbon materials, carbon sheets and carbon Examples include thin films and carbon cylinders. Of these, metal foil is preferred. It may be formed in a mesh-like structure. The thickness of the metal foil is arbitrary, but is usually 1 μm or more, preferably 3 μm or more, more 5 μm or more, usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm It is less than m. If the metal foil is thinner than this range, it may lack the necessary strength to function as a current collector. Yes. Conversely, if the metal foil is thicker than this range, its handling may be impaired.
[0118] Furthermore, the fact that a conductive additive is applied to the surface of the current collector also affects the electrical connection between the current collector and the positive electrode compound sheet. This is preferable from the viewpoint of reducing contact resistance. Suitable conductive additives include carbon, gold, platinum, silver, and other precious metals. Metals are one example.
[0119] The ratio of the thickness of the current collector to the positive electrode mixture sheet is not particularly limited, but (the positive electrode mixture sheet on one side) The value of (thickness) / (thickness of the current collector) is preferably 20 or less, and more preferably 15 or less. Below, most preferably it is 10 or less, more preferably 0.5 or more, and more preferably 0. The range is 8 or more, most preferably 1 or more. If it exceeds this range, charging and discharging will occur at a high current density. During operation, the current collector may generate heat due to Joule heating. Below this range, the positive electrode activity... The volume ratio of the current collector to the material increases, which may reduce the battery's capacity.
[0120] The positive electrode can be manufactured by conventional methods. For example, the electrode mixture sheet and the current collector can be bonded together with an adhesive. Methods include stacking the materials and then vacuum drying them.
[0121] The area of the positive electrode compound sheet is determined from the perspective of improving stability at high power and high temperatures, and the battery casing case It is preferable to increase the outer surface area. Specifically, the surface area of the secondary battery casing It is preferable that the total area of the electrode mixture on the positive electrode is 15 times or more in area ratio, and furthermore 40 It is more preferable to make it more than double. The outer surface area of the battery casing refers to the case of a bottomed rectangular shape. This refers to the length, width, and thickness dimensions of the case portion containing the power generation element, excluding the protruding terminals. This refers to the total area calculated from the terminals. In the case of a bottomed cylindrical shape, it refers to the power generation area excluding the terminal protrusions. This is the geometric surface area of the case portion filled with the material, approximating it as a cylinder. (Positive electrode electrode mixture area) The sum of these is the geometric surface area of the positive electrode mixture layer facing the mixture layer containing the negative electrode active material, and the current collector In a structure in which a positive electrode mixture layer is formed on both sides via foil, the surface of each side is calculated separately. It refers to the sum of the products.
[0122] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the current collector is subtracted. The thickness of the composite sheet is preferably 10 μm or more as a minimum for one side of the current collector. More preferably 20 μm or more, and preferably 500 μm or less as an upper limit. More preferably, the particle size is 450 μm or less.
[0123] Furthermore, a positive electrode with a different composition attached to its surface may also be used. Surface-adhering substances include aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, and acid Magnesium oxide, calcium oxide, boron oxide, antimony oxide, bismuth oxide, etc. Substances, lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate , sulfates such as aluminum sulfate, lithium carbonate, calcium carbonate, magnesium carbonate, etc. Examples include carbonates and carbon.
[0124] (Negative electrode) In this disclosure, the negative electrode is composed of a current collector and an electrode mixture sheet containing the negative electrode active material. It is preferable that it be done. The material used for the negative electrode current collector can be a metal such as copper, nickel, titanium, tantalum, or stainless steel. Examples include metallic materials such as alloys thereof, and carbon materials such as carbon cloth and carbon paper. Among these, metallic materials, particularly copper, nickel, or alloys thereof, are preferred.
[0125] In terms of current collector shape, metal materials include metal foil, metal cylinder, metal coil, metal plate, and Examples include spand metal, punched metal, and foamed metal. In the case of carbon materials, carbon sheets and carbon Examples include thin films and carbon cylinders. Of these, metal foil is preferred. It may be formed in a mesh-like structure. The thickness of the metal foil is arbitrary, but is usually 1 μm or more, preferably 3 μm or more, more 5 μm or more, usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm It is less than m. If the metal foil is thinner than this range, it may lack the necessary strength to function as a current collector. Yes. Conversely, if the metal foil is thicker than this range, its handling may be impaired.
[0126] The negative electrode can be manufactured by conventional methods. For example, the electrode mixture sheet and the current collector can be bonded together with an adhesive. Methods include stacking the materials and then vacuum drying them.
[0127] The density of the negative electrode mixture sheet is preferably 1.3 g / cm³. 3 More preferably 1.4g / cm 3 More preferably 1.5 g / cm³ 3 The above applies, and preferably 2.0 g / cm 3 More preferably, 1.9 g / cm³ 3 More preferably, 1.8 g / cm³ 3 Below The range is shown below. Exceeding this range degrades the charge / discharge characteristics, especially at high current densities, resulting in lower power output. In some cases, this may not be possible. Also, if the value falls below a certain level, the conductivity between the active materials decreases, increasing the battery resistance and thus the output. It may not be possible to obtain it.
[0128] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the current collector is subtracted. The thickness of the composite sheet is preferably 10 μm or more as a minimum for one side of the current collector. More preferably 20 μm or more, and preferably 500 μm or less as an upper limit. Preferably, the particle size is 450 μm or less.
[0129] (The elemental ratio of fluorine to carbon (F / C ratio)) The binder of this disclosure has an elemental ratio of fluorine to carbon (F / C ratio) of 0.40 or more and 3.00 or less. It is preferable that it be 0.50 or more and 2.50 or less. Being within a certain range is preferable because it allows for the manufacture of electrodes with high strength and low electrode resistance. The elemental analysis values were measured using standard, general methods. Specifically, the F / C ratio is For example, using MICRO CORDER JM10 (manufactured by J Science Lab), the sample volume is 2 mg, and burning Calcination furnace 950°C, reduction furnace 550°C, helium flow rate 200 mL / min, oxygen flow rate 15-25 CHN is measured simultaneously under mL / min conditions, and the average value of four measurements is used to determine the result. can. F / C ratio = average F(wt%) / average C(wt%)
[0130] (Solid secondary battery) This disclosure also relates to a solid-state secondary battery using the above-mentioned solid-state secondary battery additive sheet. The solid-state secondary battery of this disclosure is more preferably an all-solid-state secondary battery. The solid-state secondary battery is preferably a lithium-ion battery. The battery is preferably a sulfide-based solid-state secondary battery. The above-mentioned solid-state secondary battery comprises a positive electrode, a negative electrode, and a solid electrode interposed between the positive electrode and the negative electrode. A solid secondary battery comprising a desaturates layer, wherein the positive electrode and / or negative electrode are the solid secondary battery of the present disclosure described above. This product contains sheets for the next generation of batteries, including a positive electrode sheet and a negative electrode sheet.
[0131] The above-mentioned solid electrolyte layer is made by forming a solid electrolyte into a sheet, and is used to create a solid-state secondary battery. This layer is essential for that purpose. Solid electrolytes are used to form such a solid electrolyte layer. The solution sheet is not particularly limited and any publicly available one can be used. Furthermore, the sheet material may be obtained using PTFE as a binder. Specifically, A composition containing PTFE resin and a solid electrolyte is treated in the same manner as described herein. By fibrillating PTFE, a solid electrolyte sheet can be used. ru.
[0132] Solid-state secondary battery using electrodes obtained by the manufacturing method of a solid-state secondary battery sheet in this disclosure The laminated structure comprises a positive electrode having a positive electrode sheet and a positive electrode current collector, and a negative electrode sheet and a negative electrode current collector. It is preferable that the negative electrode comprises a positive electrode and a solid electrolyte layer sandwiched between the positive electrode and the negative electrode. stomach. The following details the separator and battery case used in the solid-state secondary battery related to this disclosure. I will explain it to them.
[0133] (Separator) The above solid secondary battery may include a separator between the positive and negative electrodes. Examples of materials include porous membranes such as polyethylene and polypropylene; and polypropylene. Examples include nonwoven fabrics made of resin, nonwoven fabrics made of glass fiber, and other nonwoven fabrics.
[0134] (Battery design) The above solid-state secondary battery may further include a battery case. The shape of the above battery case is Therefore, any container that can house the positive electrode, negative electrode, sulfide-based electrolyte layer for solid-state batteries, etc., as described above, is particularly suitable. While not limited to these, specifically, cylindrical, square, coin-shaped, laminated, etc. It can be listed.
[0135] The above method for manufacturing a solid-state secondary battery involves, for example, first, the positive electrode, solid electrolyte layer sheet, and negative electrode The batteries may also be made into solid-state rechargeable batteries by stacking them sequentially and pressing them together. By using the above-mentioned solid-state secondary battery composite sheet, a solid-state secondary battery can be produced with low moisture content in the system. It is possible to manufacture secondary batteries, and to produce solid-state secondary batteries with good performance. It is suitable. (Percentage of electrode combination group) A battery using electrodes manufactured by the method for manufacturing solid-state secondary battery sheets of this disclosure is an electric battery. The ratio of the volume of the electrode mixture group to the internal volume of the battery (hereinafter referred to as the electrode mixture group occupancy rate) is usually It should be 40% or more, preferably 50% or more, and usually 90% or less, and 80% or less. preferable.
[0136] If the electrode mixture group occupancy rate falls below the above range, the battery capacity will decrease. Also, if it exceeds the above range... When it rotates, the air gap space decreases, and the battery becomes hot, causing the components to expand or the electrolyte to... The internal pressure increases due to factors such as the vapor pressure of the liquid components, which affects the battery's charge-discharge cycle performance. This can reduce various properties such as high-temperature storage, and furthermore, the gas release valve that releases internal pressure to the outside may activate. It may happen.
[0137] In the case where the electrode mixture group has the above-described layered structure, the metal core portions of each electrode mixture layer are bundled together and welded to the terminal. A structure formed in this way is preferably used. When the area of a single electrode mixture is large, Since the resistance increases, it is also preferable to reduce the resistance by providing multiple terminals within the electrode mixture. Used. In the case of electrode mixtures with the above wound structure, multiple rings are used in the positive and negative electrodes, respectively. By creating a cord structure and bundling the wires at the terminals, the internal resistance can be reduced.
[0138] The material of the outer casing is not particularly limited as long as it is a material that is stable with respect to the electrolyte used. Physically, nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium Metals such as nesium alloys, or laminated films of resin and aluminum foil (laminate film) ) is used. From the perspective of weight reduction, aluminum or aluminum alloy metal, laminate A film is preferably used.
[0139] In exterior cases using metals, laser welding, resistance welding, and ultrasonic welding are used to weld the metals together. A sealing structure is created by welding, or the above metals are used via a resin gasket. One example is a crimped structure. Examples include those that create a sealed and airtight structure by heat-fusing resin layers together. To improve performance, a different resin than the one used in the laminate film is placed between the above resin layers. An intermediary may be used. In particular, when a sealed structure is formed by heat-sealing the resin layer via the current collection terminal. Since this involves bonding metal and resin, the intervening resin should be a resin with polar groups or a resin with polar groups. The introduced modified resin is preferably used.
[0140] The shape of the secondary battery in this disclosure is arbitrary, and for example, cylindrical, prismatic, laminated, or coin-shaped. Examples include large shapes. The shapes and configurations of the positive electrode, negative electrode, and separator are as follows: It can be used by changing the shape of the battery according to the battery type. [Examples]
[0141] The present disclosure will be described in detail below based on examples. In the following examples, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "quality," respectively. This represents "amount in percentage."
[0142] [Example 1] Referencing example 2 of International Publication No. 2015-080291, prepare a PTFE aqueous dispersion (solid). A 31.2% mass PTFE-A sample was obtained. The measured standard specific gravity was 2.16.
[0143] [Example 2] Referencing example 3 of International Publication No. 2015-080291, prepare a PTFE aqueous dispersion (solid A 30.9% mass PTFE-B was obtained. The amount of fluorine-containing surfactant used in the final PTFE The yield was 3290 ppm. The measured standard specific gravity was 2.15.
[0144] [Example 3] Based on example 1 of international publication No. 2012 / 086710, aqueous dispersion of modified PTFE. body P TFE-C was obtained. The polymer concentration of the obtained aqueous dispersion was 30.1% by mass, and the average primary particle size was 30.1%. The diameter was 0.18 μm. The measured standard specific gravity was 2.16.
[0145] [Example 4] Referencing Preparation Example 1 of International No. 2012-063622, an aqueous dispersion of PTFE particles P TFE-D was obtained. The measured standard specific gravity was 2.19.
[0146] Weigh out 0.25 g of Li-100 (acetylene black) as a conductive additive, and use it as a solvent. Add ultrapure water and mix with a mixer at 2000 rpm for 3 minutes to prepare the conductive additive dispersion. Then, 4.75g of aqueous dispersion PTFE-A was added as solid content, and then ultrapure water was added. In addition, the concentration of solids was adjusted. The final amount of solvent was 45g, after which mixed raw materials were used. The mixture was stirred in a tar for 1 hour to prepare it. Then, a spray dryer (manufactured by Tokyo Rikakikai Co., Ltd.) was used. A dried powder was obtained (inlet temperature 140°C, airflow 0.60 m³ / min, flow rate 5.5 g / min). Furthermore, vacuum drying (100°C, 8 hours) was performed to obtain binder 1. As shown in Table 1, the type and amount of PTFE aqueous dispersion, the type and amount of conductive additive, and the amount of solvent were changed, and the binding was Agents 2-11 were obtained. In Table 2, FT7000 is (multiwalled carbon nanotube). The moisture content of binders 1 to 11 was measured, and all were found to be 250 PPM or less.
[0147] [Table 1]
[0148] [Example 5] Dilute the aqueous dispersion PTFE-D obtained in Preparation Example 4 to a solid content concentration of 15% in a container equipped with a stirrer. The PTFE was gently stirred in the presence of nitric acid to solidify. The solidified PTFE was then divided. Remove and dry at 160°C for 18 hours to obtain PTFE-E in powder form without conductive additives. Ta.
[0149] <Preparation of the composition for the positive electrode> The following work was performed in an Ar atmosphere. Li(Ni) as the active material 0.6 Mn 0.2 Co 0.2 )O2, sulfide solid electrolyte (30 LiI·70 (0.75Li2S·0.25P2S5), Li-100 as a conductive additive. Then, binder 1 was added to the container. The composition of the added material was:active material:electrolyte:conductive additive (including conductive additive within the binder):binding agent = 70 The ratio was set to 28:1:1. The mixture was stirred in a mixer at 1500 rpm for 10 minutes to obtain the mixture. Add the prepared binder 1 to the container containing the mixture, and stir in a kneader at 40 rpm for 2 hours. A mixed powder composition was obtained. The resulting mixed powder composition was rolled into a sheet using metal rolls. Afterward, the rolled sheet obtained earlier is roughly crushed by folding it in half, and then returned to a bulk state. After shaping, it is pressed into a sheet using a metal roller on a hot plate heated to 80 degrees Celsius. The process of extending the mixture to promote fibrillation was repeated six times. Afterward, the cathode mixture sheet was formed. The material was cut into 5cm x 5cm pieces and placed into a roll press machine heated to 80 degrees Celsius, under a load of 10kN. By applying this process, a 400 μm thick positive electrode mixture sheet was obtained.
[0150] [Evaluation of ionic conductivity] The solid electrolyte sheet prepared above was cut into a disc shape with a diameter of 13 mm, and a circle with a diameter of 14 mm. Aluminum foil cut into a sheet is brought into contact with the solid electrolyte layer, and spacers and washers are incorporated. Then, I put it in a stainless steel 2032 type coin case. As shown in Figure 1, the coin case A cell for measuring ionic conductivity was fabricated by applying a restraining pressure (screw tightening pressure: 8N) from the outside of the device. Specifically, after being left to stand in a 30°C constant temperature bath for 1 hour, SOLARTRON's impedance Using a dance analyzer, the voltage amplitude was set to 5mV, and the frequency was measured from 1MHz to 1Hz. Impedance was measured. This determined the resistance in the film thickness direction of the sample, and the following formula was used to calculate ion The conductivity was determined. Ionic conductivity (mS / cm) = 1000 × sample film thickness (cm) / (resistance (Ω) × sample surface) Product (cm 2 ))
[0151] [Intensity Measurement] Tensile testing machine (Shimadzu Corporation Autograph AGS-X series AGS-100NX) Using this method, under conditions of 100 mm / min, a 10 mm wide strip-shaped positive electrode mixture sheet test piece was used. Measurements were taken. The distance between chucks was set to 30 mm. Displacement was applied until fracture occurred, and the measurement results were as follows: The maximum stress was used as the strength for each sample. Comparative Example 1 was set to 100 for comparison.
[0152] (Examples 2-11) A positive electrode mixture sheet was obtained in the same manner as in Example 1, except that a binder with the composition shown in Table 1 was used.
[0153] (Comparative Example 1) The cathode mixture sheet was the same as in Example 1, except that powdered PTFE-E without conductive additives was used. I got the T.
[0154] [Table 2]
[0155] The fibril diameters of Examples 5, 6, 7, 8, and 10 were measured, and the median fibril diameter was The wavelengths were 37nm, 32nm, 37nm, 51nm, and 37nm respectively.
[0156] The example shows that electrodes with higher tensile strength and good ion conductivity can be fabricated. If the degree is high, it is possible to reduce the amount of binder added and increase the amount of active material. By using a binder that is a powder that does not contain electrode active material, the battery characteristics can be improved. They discovered that. [Industrial applicability]
[0157] The electrode for a solid secondary battery obtained by the method for manufacturing an electrode for a solid secondary battery of this disclosure is an electrode This allows for reduced resistance and can be suitably used in solid-state secondary batteries.
Claims
1. The powder is made of a composition essentially containing a polytetrafluoroethylene resin and a conductive assistant, and does not contain an electrode active material. A binder for a solid secondary battery, characterized in that it is in the form of particles granulated by spray drying.
2. 2. The binder for a solid secondary battery according to claim 1, wherein an elemental ratio of fluorine to carbon (F / C ratio) measured by elemental analysis is 0.4 or more and 3.0 or less.
3. A method for producing the binder for a solid secondary battery according to claim 1, comprising: A method for producing a binder for a solid secondary battery, comprising: a step (A) of mixing PTFE and a conductive assistant in the presence of a liquid medium; and a step (B) of drying the composition obtained by the step (A) by spray drying.
